2015
DOI: 10.1088/0029-5515/55/5/053032
|View full text |Cite
|
Sign up to set email alerts
|

Integrated core–SOL–divertor modelling for ITER including impurity: effect of tungsten on fusion performance in H-mode and hybrid scenario

Abstract: The compatibility of two operational constraints-operation above the L-H power threshold and at low power to divertor-is examined for ITER long pulse H-mode and hybrid scenarios in integrated core-SOLdivertor modelling including impurities (intrinsic Be, He, W and seeded Ne). The core thermal, particle and momentum transport is simulated with the GLF23 transport model tested in the self-consistent simulations of temperatures, density and toroidal rotation velocity in JET hybrid discharges and extrapolated to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…separatrix density, radial anomalous transport). In line with our earlier simulations for JET-ILW [20,21] and ITER [22], in the case of JT-60SA it has also been found that the increased radial…”
Section: Results For the W Divertorsupporting
confidence: 90%
See 1 more Smart Citation
“…separatrix density, radial anomalous transport). In line with our earlier simulations for JET-ILW [20,21] and ITER [22], in the case of JT-60SA it has also been found that the increased radial…”
Section: Results For the W Divertorsupporting
confidence: 90%
“…separatrix density, radial anomalous transport). In line with our earlier simulations for JET-ILW [20] and ITER [22] also in the case of JT-60SA it has been found that the increased radial diffusion (D SOL = 1 m 2 /s, open symbols in Fig.5) improves the impurity retention in the SOL leading to the increased divertor radiation losses and easier access of detachment. Similar effect on the results has the increased edge density.…”
Section: Results For W Divertorsupporting
confidence: 89%
“…The COREDIV code, which solves self-consistently the radial 1D plasma energy and particle transport in the core region and 2D multi-fluid transport in the SOL region, can be used for this purpose. The code package has already been successfully used to benchmark against numerous discharges in various existing tokamaks [20][21][22][23] and to make predictions for future fusion devices [24][25][26][27]. In the following, the COREDIV model related to current study is briefly introduced.…”
Section: Modelling Methodsmentioning
confidence: 99%
“…The core plasma profiles with a range of pedestal densities are simulated by the physics-based transport solver implemented in the OMFIT (one modeling framework for integrated tasks) framework [19]. Since f burnup depends strongly on both core and SOL plasma conditions, numerical analysis of f burnup is performed by using the core-SOL coupling COREDIV code [20][21][22][23][24][25][26][27]. By adjusting the transport coefficients, COREDIV is used to match the core profiles obtained by OMFIT, and the resulting heat and particle fluxes across the boundary are used as input to simulate the SOL region.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the COREDIV simulations, we have already performed a number of simulations to investigate the influence of the SOL radial transport on simulation results. It has been done for present day experiments (JET[jet- [7,17], ASDEX-U [18]) and for future devices (ITER [19], DEMO [20]). The main conclusion from these simulations is that the stronger radial transport in the SOL helps to keep the impurities in the SOL and leads to the increased impurity radiation in the SOL.…”
mentioning
confidence: 99%